2016
DOI: 10.4274/tjo.71354
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Course of Patients with Peripheral Exudative Hemorrhagic Chorioretinopathy

Abstract: Objectives:To evaluate the clinical characteristics of patients who were followed in our clinic with the diagnosis of peripheral exudative hemorrhagic chorioretinopathy (PEHC).Materials and Methods:Medical records of 12 patients who were diagnosed with PEHC in İstanbul University İstanbul Faculty of Medicine, Department of Ophthalmology between July 2006 and June 2014 were reviewed retrospectively.Results:This study included 21 eyes of 12 patients. Four (33.3%) of the patients were male and 8 (66.7%) were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
4
0
4
Order By: Relevance
“…Demographic characteristics and past medical history of our cohort resembled previous descriptions of PEHCR [9,10,14]. An interesting finding was the relatively high prevalence of past malignancy in our cohort (10/32 patients, 31.25%), which has not been mentioned in previous reports of PEHCR.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Demographic characteristics and past medical history of our cohort resembled previous descriptions of PEHCR [9,10,14]. An interesting finding was the relatively high prevalence of past malignancy in our cohort (10/32 patients, 31.25%), which has not been mentioned in previous reports of PEHCR.…”
Section: Discussionsupporting
confidence: 79%
“…Several treatment modalities for PEHCR have been suggested previously, including cryotherapy, laser photoablation and anti-VEGF injections, with no statistically significant impact of either method thus far [8,10,15]. Previous reports have suggested intravitreal anti-VEGF injections as a treatment method to halt PEHCR progression and induce remission, especially in cases involving the macula or extending over a large area [7,9,[14][15][16][17][18]. Except for one [18], all these reports were limited by short follow-up periods and small sample size (1 to 12 eyes), but demonstrated a favorable response to 2-3 injections, with resolution of subretinal fluid, hemorrhages, and some improvement in VA (although not statistically significant), sometimes requiring an additional injection if recurrence was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 11 ] As noted in our case, it is present more often in patients with hypertension and those treated with anticoagulants. [ 5 12 13 ] Annesley reported anticoagulant therapy to be a risk factor for the extended involvement. [ 12 ] The common macular complications include drusens, RPE alterations, macular edema, and epiretinal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have suggested that PEHCR is the peripheral variant of age-related macular degeneration, with an underlying choroidal vascular network responsible for its pathophysiology. 5,6 This is because age-related macular degeneration features, including drusen, RPE abnormalities, and choroidal neovascularization, are often observed in PEHCR, and the exudative nature of the lesions observed in both conditions are similar. Some researchers have suggested that PEHCR is a subtype of polypoidal choroidal vasculopathy (PCV).…”
mentioning
confidence: 99%